Hydronephrosis due to a supernumerary ovarian and uterus - Ferraz, A. (2011)
Introduction Hydronephrosis is a distention and dilation of the renal pelvis, usually caused by obstruction of the free flow of urine from the kidney, leading to progressive atrophy of the kidney. The obstruction of urine outflow can happen at any site from the renal pelvis to the urethral orifice. Unilateral hydronephrosis may occur without any symptoms. Material and Methods A seven month old european cat, was present to the clinic for vaccination. The routine physical examination revealed a palpable mass in the cranial abdomen. Severe left hydronephrosis was diagnosed after clinical, radiographical and ultrasonographical examination. The cat wasn’t azotemic. Surgery was necessary to reach a final aetiological diagnosis and treatment. A left ureteronephrectomy and ovariohysterectomy were performed. The cat kept the renal function, without serum increase in urea and creatinine, with no postoperative complications. Results At macroscopical examination, when the sample was sectioned longitudinally, some underdeveloped female genital organs, were observed, near the renal hilum. The histopathological analysis revealed a kidney with a very thin wall and clear atrophy of the cortical region, fibrosis of the ureter and a supernumerary ovary and uterus (adjacent to renal hilum). Discussion/Conclusion The occurrence of supernumerary ovaries has been observed in the cat and they are most frequently located on the broad ligament within 1 to 4 cm from the ovary but not in the localization described in the present case. To the author’s knowledge, this is the first case of double uterus and supernumerary ovarian to cause hydronephrosis. The ureteronephrectomy was successful in treating the animal.